Ionic Liquids with Multi‐Active Sites Synergistically Catalyzed Metal‐Free Transformation of Alcohols Using Dimethyl Carbonate as an Environmental Solvent. Issue 27 (19th July 2021) - Li, Zengmin; Wen, Yating; Wang, Ning; Han, Feng; Li, Ying; Zhuang, Hongfeng; Miao, Chengxia
Abstract: One of the ultimate goals in organic synthesis is to develop metal‐free, efficient and easily separable catalytic system for atom economic organic reactions in an environmental solvent. Direct substitution reaction of alcohols and hydrocarbon compounds is a significant and atom economic method for C−C bond formation. Herein, a metal‐free and efficient catalytic system including recyclable pyridine‐based ionic liquids with multiple active sites as the catalyst and dimethyl carbonate as the environmentally friendly solvent was developed for atom economic C3 substitution of 4‐hydroxycoumarins with alcohols. Primary aromatic alcohols, secondary aliphatic and aromatic alcohols were suitable for the reaction, providing up to 99 % yield. The catalytic system could be easily scaled up to gram‐scale with nearly quantitative yield. Coumatetralyl as commercial rodenticide could be prepared directly from commercially available 4‐hydroxycoumarin and 1, 2, 3, 4‐tetrahydronaphthalen‐1‐ol. Racemic product derived from the reaction of ( R )‐1‐phenylethanol and 4‐hydroxycoumarin indicated the reaction was achieved through an SN 1 pathway. The comparison of the activities and acidities of the ionic liquids demonstrated that there was no directly relationship between them. Control experiments showed that the reaction probably proceeded via carbocation, ether intermediate and synergistically promoted effect of hydrogen bonding between the ionic liquid with multi‐active sites and substrates. Abstract : Pyridine‐based ionic liquids with multiple active sites synergistically catalyzed C3 substitution of 4‐hydroxycoumarin with alcohols in dimethyl carbonate was demonstrated. The system was efficient, economic and environmental and successfully applied for the synthesis of coumatetralyl as commercial rodenticide. And a mechanism involving a SN 1 pathway, synergistically promoted effect of hydrogen bonding, carbocation and ether was proposed.